2013
DOI: 10.1103/physrevb.87.205115
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the electronic structure differences between polar isostructural FeO and CoO films by core-level soft x-ray spectroscopy

Abstract: The electronic properties of the FeO and CoO single layer thin films on Pt(111) were examined by core level soft X-ray spectroscopy. These oxygen terminated films are bilayer-thick and isostructural, Pt, Fe-Co, and O atoms stacked with small lateral shifts due to incommensurate relation with Pt(111). Probing occupied and unoccupied states projected on the oxygen atoms revealed states at the Fermi level suggesting orbital mixing with the metal substrate and also indicated an anisotropy in transition metal-oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Bulk electronic and magnetic structures of Fe 3 O 4 and Fe 2 O 3 have been investigated by XPS and XAS (and also by electron energy loss spectroscopy), many studies on the interpretation of O K-edge and Fe L-edge XAS spectra have been reported [15,[17][18][19][20][21]. Although there are few surface sensitive XPS measurements [22], so far no systematic XAS investigations on the local coordination and electronic structures of the surface atoms terminating iron oxide single crystal surfaces have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk electronic and magnetic structures of Fe 3 O 4 and Fe 2 O 3 have been investigated by XPS and XAS (and also by electron energy loss spectroscopy), many studies on the interpretation of O K-edge and Fe L-edge XAS spectra have been reported [15,[17][18][19][20][21]. Although there are few surface sensitive XPS measurements [22], so far no systematic XAS investigations on the local coordination and electronic structures of the surface atoms terminating iron oxide single crystal surfaces have been performed.…”
Section: Introductionmentioning
confidence: 99%